Narrow ovale foramina may be involved in the development of primary trigeminal neuralgia - Li, Shuo; Liao, Chenlong; Qian, Meiqiong; Yang, Xiaosheng; Zhang, Wenchuan (Frontiers in Neurology, 2022)
Background The etiology of primary trigeminal neuralgia remains unclear and is worthy of further study; In this study, the morphometric characteristics of ovale foramina between various groups were compared and analyzed to explore the novel cause of primary trigeminal neuralgia. Methods High-resolution three-dimensional reconstruction images from head computed tomography of 109 patients with primary trigeminal neuralgia affecting the third branch of the trigeminal nerve and 46 healthy controls were retrospectively reviewed. Among the 109 primary trigeminal neuralgia patients, 79 patients with apparent neurovascular compression (not simply contact) demonstrated on MRI or during surgery were divided into the classical trigeminal neuralgia group and 30 patients with MRI showing no significant abnormalities were divided into idiopathic trigeminal neuralgia group. The morphometric parameters including the area, width and length of ovale foramina were examined through the use of radiologic methods. Results In this study, the average minimum area, width and length of 79 ovale foramina on the affected and unaffected sides in the classical trigeminal neuralgia group were 21.83 ± 8.45, 21.94 ± 7.93 mm2, 2.32 ± 0.91, 2.58 ± 0.81, 5.32 ± 1.29, and 5.26 ± 1.21 mm, respectively. No significant difference in these parameters was observed (p > 0.05). However, in the idiopathic trigeminal neuralgia group, the average minimum area, width and length of 30 ovale foramina were 21.33 ± 8.21, 22.85 ± 8.36 mm2, 2.25 ± 0.90, 2.79 ± 0.96, 5.20 ± 1.27, and 5.28 ± 1.19 mm, respectively. The width on the symptomatic side was significantly smaller (p = 0.03) than that on the asymptomatic side. No significant difference in area (p = 0.48) or length (p = 0.79) was observed. In addition, when compared with the healthy control group, the area and width of ovale foramina on the symptomatic side in both groups were significantly smaller. No significant difference in length was observed. Conclusions By comparing and analyzing the statistical data, it can be inferred that a narrow foramen ovale is associated with primary trigeminal neuralgia, as well as its recurrence after microvascular decompression.